Epistemically robust strategy subsets - Geir B. Asheim; Mark Voorneveld; Jörgen W. Weibull (University of Oslo, Department of Economics, 2016)
We define a concept of epistemic robustness in the context of an epistemic model of a finite normal game where a player type corresponds to a belief over the profiles of opponent strategies and types. A Cartesian product X of pure strategy subsets is epistemically robust if there is a Cartesian product Y of player type subsets with X as the associated set of best reply profiles such that the set Yi contains all player types that believe with sufficient probability that the others are of types in Y-i and play best replies. This robustness concept provides epistemic foundations for set-valued generalizations of strict Nash equilibrium, applicable also to games without strict Nash equilibria. We relate our concept to closedness under rational behavior and thus to strategic stability and to the best reply property and thus to rationalizability.
Keywords: C72; D83; 330; epistemic game theory; epistemic robustness; rationalizability; closedness under rational behavior; mutual p-belief